ANALISIS TINDAK TUTUR DALAM NOVEL DOMPET AYAH SEPATU IBU KARYA J.S KHAIREN - Gifelem, Agustinus Gideon; Howay, Regina (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to find out the form of illocutional speech contained in the novel